Combinatorial Passivation Study in the Aluminium-Samarium System for Basic Property Mapping and Identification of Secondary Phase Influence. Issue 1 (22nd January 2021) - Yamamoto, Yudai; Mardare, Andrei Ionut; Kollender, Jan Philipp; Mardare, Cezarina Cela; Recktenwald, Dominik; Fushimi, Koji; Hassel, Achim Walter
Abstract : An aluminium-samarium binary library with a varying Sm concentration between 4 to 14 at.% was produced using a thermal co-evaporation technique. Morphological and crystallographic characterization of the parent metal alloys revealed compositionally dependent surface structure and atomic arrangements. Grains resembling pure Al on the surface slowly disappeared with increasing Sm content and above 8 at.% Sm nucleation of the AlSm2 intermetallic phase was observed. Scanning droplet cell microscopy was used for a comprehensive electrochemical characterization along the Al-Sm compositional gradient. Anodic oxide formation under high field conditions was discussed for alloys below the compositional threshold of 8 at.% Sm. Above this threshold a continuous increase of Sm dissolution during anodization with increasing Sm concentration was proven by inductively coupled plasma optical emission spectroscopy. Coulometry followed by EIS allowed mapping of the oxide formation factors and oxide electrical permittivity as material constants for single Al-Sm alloys. A small increase of both material constants for alloys below the compositional threshold described the Sm contribution to the anodization process. An apparent enhancement of their values at alloys above the threshold was directly attributed to the increased Sm dissolution rates reaching values of 2 ng cm −2 s –1 at 12 at.% Sm.